Evaluation of Certain Food Contaminants : Sixty-fourth Report of the Joint FAO/WHO Expert Committee on Food Additives. - Organization, World Health (Technical report series (World Health Organization) ;, 2006)
The monographs in this volume summarize the data that were reviewed on these contaminants, including information on metabolism and toxicity, epidemiology, analytical methods for their measurement in food commodities, sampling protocols, effects of processing, levels and patterns of contamination of food commodities, food consumption, and prevention and control. Based upon this information, the Committee assessed the risks associated with intakes of six food contaminants or groups of contaminants (acrylamide, cadmium, ethyl carbamate, inorganic tin, polybrominated diphenyl ethers (PBDEs) and po.